CINEI V1.1: Integrated Anthropogenic Emission Inventory for China - Yijuan Zhang; Mihalis Vrekoussis; Guy Brasseur (PANGAEA, 2025)
To better understand the reasons for this deterioration in air quality in several cities in China, and to assess the effectiveness of past, current and planned targeted pollution control strategies, we developed an integrated anthropogenic emissions inventory (CINEI). The CINEI emissions were derived from the existing national inventory of The Multi-resolution Emission Inventory for China (MEIC) specifically for mainland China and global inventory of The Community Emissions Data System (CEDS) for areas outside China at 0.25° resolution. In order to obtain harmonized data, our inventory takes into account differences in spatial emission mapping as same spatial resolution and source mapping (sectoral information) based on the Intergovernmental Panel on Climate Change (IPCC) activity sector. We include the power generation, transport, industry, residential sectors from national inventory (MEIC), as well as the national-omitted sectors from global inventories, which include shipping (from inventory of The Copernicus Atmosphere Monitoring Service emissions, CAMs), aviation (from inventory of Hemispheric Transport of Air Pollution, HTAP), agriculture (from HTAP), and waste (from CEDS). In addition, we applied observed source profiles for non-methane volatile organic compounds (NMVOCs) and aim to improve the representation for NMVOC speciation. NMVOC speciation is unified as the Model for Ozone and Related chemical Tracers mechanism (MOZART), which is widely used by global and regional chemistry and transport models (CTMs). CINEI includes 8 sectoral emission, 25 species (inorganic gas, NMVOCs gas, and particulate matter), and covers east Asia (70.125°E to 149.875°E and 10.125°N to 59.875°N). The CINEI dataset provides monthly data in 2017, with 0.25 spatial resolution. Therefore, our CINEI inventory improves the representation in emission sectors and spatial distribution, and facilitates the simulation in CTMs.